1997
DOI: 10.2337/diab.46.11.1786
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Intakes of Supplemental Chromium Improve Glucose and Insulin Variables in Individuals With Type 2 Diabetes

Abstract: Chromium is an essential nutrient involved in normal carbohydrate and lipid metabolism. The chromium requirement is postulated to increase with increased glucose intolerance and diabetes. The objective of this study was to test the hypothesis that the elevated intake of supplemental chromium is involved in the control of type 2 diabetes. Individuals being treated for type 2 diabetes (180 men and women) were divided randomly into three groups and supplemented with: 1) placebo, 2) 1.92 micromol (100 microg) Cr a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
282
4
9

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(308 citation statements)
references
References 17 publications
13
282
4
9
Order By: Relevance
“…Three of the reviewed trials reported on adverse events. [45][46][47] All of these demonstrate the absence of adverse events in participants receiving chromium picolinate.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Three of the reviewed trials reported on adverse events. [45][46][47] All of these demonstrate the absence of adverse events in participants receiving chromium picolinate.…”
Section: Resultsmentioning
confidence: 86%
“…44 Ten trials met all inclusion criteria and provided data for body weight that were suitable for statistical pooling (Table 1). Seven other studies, which were reported in six articles, [45][46][47][48][49][50] were also included but reported data that were not suitable for statistical pooling ( Table 2). None of these trials reported a significant reduction of body weight in participants treated with chromium picolinate compared with placebo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it was difficult to ascertain whether there was a supplementation effect. The trial by Anderson et al, 18 done in China using very high doses of chromium picolinate (1000 mg/ d), was larger (n ¼ 60) and longer (16 wk) than the prior study. However, it also used a per-protocol design that focused only on completers (52 of 60) in the 1000-mg arm, and so here, too, the principles of randomization were violated.…”
Section: Studies Measuring Fasting Plasma Glucosementioning
confidence: 88%
“…20 This complex of molecules found in high amounts in brewer's yeast and other foods functions synergistically to potentiate the effects of insulin [21][22][23] by increasing insulin binding to cells, upregulating receptors, and improving affinity. 24 Some reports suggest that chromium could suppress appetite and stimulate thermogenesis through sensitization of insulin-sensitive glucoreceptors in the brain. 25 Body fat distribution is related to insulin sensitivity; peripheral fat is more insulin sensitive than central fat found in the chest and abdomen.…”
Section: Introductionmentioning
confidence: 99%